2020
DOI: 10.5334/jime.589
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Pronunciation LMOOC in Higher Education Studies

Abstract: This paper examines the creation and running of the Language MOOC (LMOOC) "The Acquisition of English Pronunciation through Songs and Literary Texts" (1 st ed.) and its effects on the proficiency rates of English pronunciation of a group of Spanish speakers registered in the Degree in English Studies offered at the Distance Learning University in Spain (UNED). The LMOOC included a new approach to phonetics teaching and learning based on the stress and rhythmic patterns of literary and music forms. It was offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this case, MOOC will allow us to expand the possibilities of face-to-face learning [15] and ensure a balance between that learning and online education [16]. As it is stated in the work of Estebas-Vilaplana and Solans [31], the implementation of MOOC at the level of regulatory documents is quite a problematic task, since the curriculum has permanent educational components. We believe that according to the principle of academic freedom, every teacher within the limits of his/her discipline can encourage students to take online courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, MOOC will allow us to expand the possibilities of face-to-face learning [15] and ensure a balance between that learning and online education [16]. As it is stated in the work of Estebas-Vilaplana and Solans [31], the implementation of MOOC at the level of regulatory documents is quite a problematic task, since the curriculum has permanent educational components. We believe that according to the principle of academic freedom, every teacher within the limits of his/her discipline can encourage students to take online courses.…”
Section: Discussionmentioning
confidence: 99%
“…Audio files, including authentic English songs [3], are also effective educational content for learning English. In this context, Estebas-Vilaplana and Solans [31] applied the method of studying phonetics with the help of MOOC, during which the stress and rhythm of musical and literary forms are studied. Sometimes online courses offer practical tasks with further verification by the course developer.…”
Section: B Key Features Of Using Mooc In Language Learningmentioning
confidence: 99%
“…The study showed that learners' comprehensibility benefits from feedback and that students improve more if provided with individualized and frequent feedback from different sources. Estebas-Vilaplana and Solans (2020) found that the LMOOC "The Acquisition of English Pronunciation through Songs and Literary Texts" had a positive effect on the production skills of Spanish students of English, especially in the prosodic features such as rhythm and stress as well as phonetic transcription reading. In the final oral exam MOOC participants outperformed the students who used regular course materials.…”
Section: Introductionmentioning
confidence: 98%
“…The research on the effectiveness of MOOC on oral skills and in particular pronunciation is scarce. The foreign languages which have been examined in MOOC-based pronunciation research include Japanese (Marciniak, 2018) and Spanish (e.g., Estebas-Vilaplana and Solans, 2020;Marrero-Aguiar, 2021;Rubio, 2014). Marciniak et al (2018) examined the effectiveness and validity of evaluation by peers, non-native teachers, and an independent native teacher in a Japanese pronunciation LMOOC.…”
Section: Introductionmentioning
confidence: 99%